Fiscal Policy, Monetary Policy, and Growth: The Impact of Unemployment and Inflation on Growth in Saudi Arabia (The International Journal for Scientific Research, 2024)
This paper uses time-series regression analysis to investigate the long-run effect of fiscal and monetary policies on economic growth in Saudi Arabia from 1999 to 2022. Regarding fiscal policy, we focus on government spending and exclude taxes because the latter had not been used in the Kingdom as a fiscal tool during most of the study period. For monetary policy, we focus on money supply (i.e., open market operations) and exclude interest rate, because by following a fixed-exchange-rate policy to the US dollar, the Saudi Central Bank has lost some of its monetary independence to the Federal Reserve when it comes to setting interest rates. Our results show a statistically significant positive impact of government spending on economic growth and a statistically significant negative impact of unemployment on economic growth in the long run. Also, we find the effect of money supply and inflation on economic growth in the long run to be statistically insignificant. These results are consistent with economic theory and empirical research which show countries that follow a fixed-exchange-rate policy usually lose the effectiveness of their monetary policy. Finally, we recommend taking extra care not to overuse government spending as the only tool for growth: on one hand, government spending boosts growth and lowers unemployment, but on the other, it fuels inflation and increases the national debt if it happens to be deficit spending. Therefore, it is important for Saudi Arabia to be less dependent on government spending by diversifying its income resources, creating jobs in the private sector, and creating a stable and attractive business environment for domestic and foreign investments.
Keywords: Economic Growth; Government Spending; Money Supply; Unemployment; Inflation; Fiscal Policy; Monetary Policy